1981
DOI: 10.1093/infdis/143.3.413
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Mechanisms of Neisseria gonorrhoeae: Observations on Damage to Human Fallopian Tubes in Organ Culture by Gonococci of Colony Type 1 or Type 4

Abstract: The relative virulence of isogenic clones of colony type 1 (T1) (piliated) and colony type 4 (T4) (nonpiliated) gonococci was assessed in organ cultures of human fallopian tubes. The rate of damage to fallopian tube mucosa was determined by measurements of ciliary activity and was correlated with the sequential pathologic events observed by light and electron microscopy. During the first 24 hr of the infection, T1 gonococci attached to and damaged the mucosa more rapidly than did T4 gonococci. This damage was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
136
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(144 citation statements)
references
References 27 publications
8
136
0
Order By: Relevance
“…This may have relevance in the pathogenesis of gonococcal salpingitis. In a fallopian tube model of gonococcal salpingitis, transcellular migration of gonococci with the establishment of infection in the lamina propria has been observed (38). Perhaps the organism adopts this strategy to avoid host defences or in a quest for limited nutrients, such as iron.…”
Section: Resultsmentioning
confidence: 99%
“…This may have relevance in the pathogenesis of gonococcal salpingitis. In a fallopian tube model of gonococcal salpingitis, transcellular migration of gonococci with the establishment of infection in the lamina propria has been observed (38). Perhaps the organism adopts this strategy to avoid host defences or in a quest for limited nutrients, such as iron.…”
Section: Resultsmentioning
confidence: 99%
“…We investigated whether neisserial porins can enter eukaryotic cells and interact with the mitochondria, based on the structural and functional similarities of neisserial porins and mitochondrial porins and the suggestive evidence that neisserial porins must interact with lymphocytes to induce their immunopotentiating effect. It has been shown that neisserial porins vectorially translocate into artificial membranes and target cells (41), and it has been proposed that they might bind or insert into the membrane of epithelial cells at the sites of close contact between bacteria and cells during the infection (42,43). The mechanism of translocation of the porins into the target cells is still poorly characterized, and thus there is no evidence of a specific receptor-mediated event accounting for porin.…”
Section: Discussionmentioning
confidence: 99%
“…This microorganism can also attack and destroy the non-ciliated cells of the tubal mucosa. The ensuing tissue damage stimulates the mucosa to regenerate and in the process significant amounts of proinflammatory cytokines, such as tumor necrosis factor (TNF) α are secreted into the tubal lumen [109,110]. It has been suggested that production of these pro-inflammatory cytokines, may be the mechanism by which damage to the oviduct occurs [111][112][113].…”
Section: Smokingmentioning
confidence: 99%